(untitled) (Journal of the College of Basic Education, 2022)
In light of the great progress of communication technology and the information revolution in various fields of life and the proliferation of television channels, many diverse programs targeting children have appeared, as children are considered the future wealth of every nation. And the discourse produced by the culture of the visual image may carry in its content many positive and negative effects in various aspects on members of society in general and children in particular.